Analysis and Application of Security Risk Management Based on Business Process Granularity - Bin Tan (Dianxin kexue)
Existing assets as the core of the security risk management models, cannot meet the actual needs of business risk management. Through the establishment of security granularity based on business process risk management models, and the realization and application in the WAP, SMS systems, the business risk management was realized. Security administrators and business system administrators can clearly understand the security risk situation of business systems, effectively focus and prioritize critical business systems, business processes and the security alarm; based on perceived security risk posture, security officer may plan, develop and implement safety programs, to improve operational safety risk management.